Review on Epidemiology and Public Health Importance of Goat Tuberculosis in Ethiopia - Zelalem Ayana Dibessa (Veterinary Medicine International)
Small ruminant is an important and integral part of livestock in Ethiopia. Especially, goats are attractive to people of Ethiopia because of the ability to resist challenges, easily adapt to different ecological regions, and need small land to rearing and small initial capital in which poor people can engaged in the production system. In spite of the presence of large number of goat population in Ethiopia, it fails to utilize expected productivity due to many factors. Among the factors, which limit the economic returns of goats, diseases stand frontline. Tuberculosis is one the diseases that affect goats’ health and production in Ethiopia. Goat tuberculosis is a chronic disease, which is characterized by the development of granulomas, essentially in the respiratory tract and related lymph nodes, from which the mycobacteria are discharged and contaminate other susceptible animals. Goat tuberculosis has a public health implication in Ethiopia because of the farmers’ habit of consuming raw goat milk and its products, and they do have consistent or day-to-day contact with their goats. The etiological agents also transmitted to humans through the aerogenous route from those animals with active cases in the herd. The infection has been reported from several parts of different areas of the country dependent on the abattoir inspections. Therefore, attention should be given towards the control of tuberculosis in livestock; public health education on zoonotic importance of the disease or awareness creation and the national tuberculosis control needs to consider the one health approach, and further epidemiological studies should be undertaken.